The Year the European Crisis Ended - Jones, E. author. aut Link
XIV, 129 p.
Keywords: The author narrates the end of the European crisis from the June 2012 European Council summit through the bailout of Cyprus. Paying particular attention to political developments in Italy, the book shows the fragility of market confidence and the waving attitudes of political elites.